Effects of complexing agents on chemically deposited Mg1-xNxS thin films - Ottih, I. (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2012)
Thin films of magnesium nickel sulphide (MgNiS) were grown on glass substrates using the chemical bath deposition (CBD) technique at room temperature. Effects of volumes of the complexing agent on the optical properties of the films were studied by depositing MgNiS thin films under different volumes of ammonia. The optical properties of the deposited films were investigated by measuring the optical absorbance of the films and the normal incident of light in a range of 200–1000 nm using a Janway 6405 UV–VIS spectrophotometer. Other properties, such as transmittance, reflectance, and energy gap, were calculated from the absorbance values. The low reflectance and large band gap make the films good materials for anti reflection coatings and absorber layers of solar cells, respectively.